2009
DOI: 10.1016/j.immuni.2009.02.006
|View full text |Cite
|
Sign up to set email alerts
|

The Intracellular Sensor NLRP3 Mediates Key Innate and Healing Responses to Influenza A Virus via the Regulation of Caspase-1

Abstract: SUMMARY Virus-induced IL-1β and IL-18 production in macrophages is mediated via a caspase-1 pathway. Multiple microbial components, including viral RNA, are thought to trigger assembly of the cryopyrin inflammasome and consequent caspase-1 activation. Here we demonstrate that cryopyrin−/− and caspase-1−/− mice are more susceptible than wildtype controls following infection with a pathogenic influenza A virus. This profile of enhanced morbidity correlates with decreased neutrophil and monocyte recruitment and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
686
5
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 659 publications
(746 citation statements)
references
References 56 publications
40
686
5
7
Order By: Relevance
“…Nlrp3 −/− , ASC −/− , and Casp1 −/− mice backcrossed to C57BL/6 background for at least 10 generations have been described previously (33,34). Mice were housed in a pathogen-free facility and the animal studies were conducted under protocols approved by St. Jude Children's Research Hospital Committee on Use and Care of Animals.…”
Section: Methodsmentioning
confidence: 99%
“…Nlrp3 −/− , ASC −/− , and Casp1 −/− mice backcrossed to C57BL/6 background for at least 10 generations have been described previously (33,34). Mice were housed in a pathogen-free facility and the animal studies were conducted under protocols approved by St. Jude Children's Research Hospital Committee on Use and Care of Animals.…”
Section: Methodsmentioning
confidence: 99%
“…Studies investigating the role of the NLRP3 inflammasome in the development of the adaptive immune response have yielded controversial results; the development of adaptive immunity was found to be mainly dependent on inflammasome activation, but was NLRP3-independent [55,56]. Recently, studies on the mechanism underlying NLRP3 activation during influenza virus infection have suggested that the priming signal for activation of the NLRP3 inflammasome is provided following the recognition of viral RNA by TLR7, with subsequent IL-1b production [57].…”
Section: Rna Virusesmentioning
confidence: 99%
“…Although several independent studies have uncovered a protective function of the inflammasome during viral infections 35,100,101 , others observed that inflammasome activation by certain viruses was mainly crucial for innate and healing response but not for virus control and adaptive immune activation. 102 Thus, the exact mechanism of virus recognition and the possible influence of genetics of inflammasomes on protection from viruses remain unclear.…”
Section: Infectionsmentioning
confidence: 99%